Tuberculosis associated factors caused by Mycobacterium tuberculosis of the RDRio genotype - Moraes, Eloise Brasil [UNESP]; Slompo, Leticia; Finardi, Amanda Juliane [UNESP]; Paro Pedro, Heloisa da Silveira; Ruiz, Luciana; Gomes, Harrison Magdinier; Richini, Virginia Bodelao; Suffys, Philip; Castelo Branco Fortaleza, Carlos Magno [UNESP]; Cavalcanti, Ricardo [UNESP]; Foschiani Dias Baptista, Ida Maria [UNESP] (Fundaco Oswaldo Cruz, 2017)
BACKGROUND Tuberculosis (TB) continues to be a disease that affects many countries around the world, including Brazil. Recently, a subtype of Latin American-Mediterranean family strain was identified and characterised by RDRio. The strain has been associated with different characteristics of the disease. OBJECTIVES In the present study we investigated the association of epidemiological, clinical, radiological and bacteriological variables with pulmonary tuberculosis caused by RDRio Mycobacterium tuberculosis strain in large regions of Sao Paulo. METHODS We conducted a cross-sectional study in 530 patients with pulmonary tuberculosis, diagnosed using sputum culture, from two regions of the Sao Paulo state in Brazil. The samples were brought to Sao Paulo reference laboratories for epidemiological, clinical, radiological and bacteriological analyses, and the data were obtained from a TB notification system. RDRio genotyping and Spoligotyping of the samples were performed. For the analysis of the categorical variables we used the chisquare test or the Fisher's exact test, and for the continuous variables, the Mann-Whitney test. In addition, a logistic regression was used for multivariate analysis. Differences with p < 0.05 were considered significant. FINDINGS The RDRio deletion was identified in 152 (28.7%) samples. In the univariate analysis, both the age groups above 25 years and alcohol consumption were associated with the RDRio deletion. The multivariate analysis confirmed the association of the RDRio deletion with the age groups: 25-35 years old [OR: 2.28 (1.02-5.07; p = 0.04)] and 36-60 years old (OR: 2.36 (1.11-5.05); p = 0.03], and also with alcohol consumption [OR: 1.63 (1.05-2.54); p = 0,03]. MAIN CONCLUSIONS In this study, we identified new factors associated with the M. tuberculosis of the RDRio deletion strains infection.
Keywords: Mycobacterium tuberculosis; RDRio; tuberculosis; genotyping; epidemiology